PENGARUH MENDONGENG TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK WALDHA ALISLAMY PEKANBARU - Risma Nofita; Wusono Indarto; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of storytelling on emotional intelligence of children aged 5-6 years in TK Waldha Al-Islamy Pekanbaru Research using experimental methods with one-group design pre-test post-test design. Population in this research that is children of class B which amounted to 20 children and sample in this research amounted to 20 anak.Teknik data collection used in this research is observation with activity of storytelling. The data analysis techniques used in this study using t test analysis. In hypothesis test in this research there is influence to emotional intelligence age 5-6 year in kindergarten Waldha Al-Islamy Pekanbaru, 419> t table = 2.093 with sig 0.000, because sig <0,05 hence can be concluded that there influence of storytelling to emotional intelligence in child . Can be interpreted that there is influence of storytelling to emotional intelligence of children aged 5-6 years in kindergarten Waldha Al-Islamy Pekanbaru significant by 42,18%. Keywords: Storytelling, Emotional Intelligence